Characterization of orbital masses by multiparametric MRI. Issue 2 (February 2016) - Ro, Sa-Ra; Asbach, Patrick; Siebert, Eberhard; Bertelmann, Eckart; Hamm, Bernd; Erb-Eigner, Katharina
Abstract: Objectives: DWI and dynamic contrast enhanced (DCE) MR imaging are techniques that allow insight to tumor vascularity and cellularity. We evaluated the diagnostic performance of multiparametric MRI (mp-MRI) in distinguishing benign from malignant orbital masses using standard anatomic imaging (sAI), DWI and DCE. Materials and methods: This prospective IRB approved study with written informed consent included 65 patients. mp-MRI at 3 Tesla including DWI and DCE was performed in all patients. Parametric maps were generated for obtaining the perfusion parameters including K trans, k ep, v e and iAUC and time-signal intensity curves were recorded to determine the curve pattern. Two radiologists rated the likelihood of malignancy on a five-point scale in three separate, randomized reading sessions (initially only sAI, afterwards sAI + either DWI or DCE and finally sAI + DWI + DCE). Data was statistically analyzed. Results: 33 Patients had malignant orbital masses and 32 patients had benign orbital masses (reference standard histopathology in 35 cases and clinical follow-up in 30 patients). The mean ADC of malignant masses differed significantly from the mean (SD) ADC of benign masses (0.825 [0.437] × 10 −3 mm 2 /s and 1.257 [0.576] × 10 −3 mm 2 /s, respectively) ( p = 0.001). K trans, k ep and iAUC were significantly higher in malignant masses ( p < 0.01). The reading of sAI only resulted in a moderate specificity but poor sensitivity in differentiating benign from malignant lesions. Adding DWI and DCE images improved specificity and sensitivity considerably, being the highest for the combined reading of all sequences. Conclusion: mp-MRI is a helpful tool in differentiating malignant orbital lesions from benign masses and should therefore be included in the routine diagnostic protocol for orbital imaging.